A 10-week implementation of the FIT FIRST FOR ALL school-based physical activity concept effectively improves cardiorespiratory fitness and body composition in 7–16-year-old schoolchildren - Olsen, Helgi Winther; Sjúrðarson, Tórur; Danielsen, Bára Berghamar; Krustrup, Peter; Larsen, Malte Nejst; Skoradal, May-Britt; Mohr, Magni (Frontiers in Public Health, 2024)
The purpose of the present study was to investigate the effect on health-related physical fitness when implementing the FIT FIRST FOR ALL school-based physical activity program on a whole school level adding 3x40 min/wk organized physical activity to the standard 60 to 120 min/wk physical education program of Faroese school children. We applied a non-randomized controlled design to investigate the effects. Two schools took part with pupils aged 7-16 yrs. (grade 1-9); one intervention school (INT; n=179) and one control school (CON; n=181). The FIT FIRST FOR ALL program consisting of 3 weekly 40-min sessions with age-adjusted high intensity physical activity was implemented for 10 weeks in INT, while CON continued their normal school program. All pupils performed pre-and post-intervention testing of cardiorespiratory fitness (Yo-Yo IR1C test), agility (Arrowhead Agility test), postural balance, and standing long jump performance as well as body composition, blood pressure and resting heart rate. A time×group effect (P<0.001) existed for changes in cardiorespiratory fitness, which increased (P<0.05) by 31% [23;39] in INT and remained unaltered in CON (7% [-2;16], P=0.13). In addition, a time×group effect (P<0.001) was observed for changes in agility, which improved (P<0.05) by 2.1% [1.0;3.2] in INT and regressed (P<0.001) by 3. 3% [2.3; 4.4] in CON. No between-group effects were observed for changes in standing long jump and balance. A time×group effect (P<0.001) was observed for changes in total muscle mass, which increased (P<0.05) by 1.4 kg [1.2;1.5] in INT and by 0.4 kg [0.3;0.6] in CON. Furthermore, a time×group effect (P<0.001) existed for total fat percentage, which decreased (P<0.05) by -2.3% [-2.8;-1.9] in INT and remained unchanged in CON (-0.3% [-0.7;0.1]). No between-group effect (P≥0.34) existed for blood pressure and resting heart rate. In conclusion, the FIT FIRST FOR ALL program markedly improved cardiorespiratory fitness and agility and induced favorable alterations in body composition in an entire school. Thus, the FIT FIRST FOR ALL program appears highly efficient to improve physical fitness and health status at school-level, with health beneficial effects for all investigated age groups.